Analisis Kegiatan Operasional dan Strategi Marketing pada Bank BRI Unit Gading Cempaka - Jagadita; Sumartono, Eko; Mujiono (Dharmakayana, 2025)
This community service activity aims to analyze operational activities and marketing strategies implemented at Bank BRI Gading Cempaka Unit based on a one-month field practice. The approach used was descriptive qualitative with data collection methods through observation, interviews, and documentation. The results show that the Teller, Customer Service, and Marketing divisions have a significant role in providing financial services and reaching the community. The 4P-based marketing strategy (Product, Price, Place, and Promotion) was implemented effectively, especially in promoting BRImo, Simpedes, and KUR products. In addition, direct interaction with customers and field surveys by marketing officers strengthened trust and expanded service access. Digital literacy is a challenge, especially for elderly customers, so face-to-face education is still very much needed. This activity provides a strategic overview for improving banking services and marketing in local work units.